2021
DOI: 10.1186/s13000-021-01123-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel TNC-PDGFD fusion in fibrosarcomatous dermatofibrosarcoma protuberans: a case report

Abstract: Background Dermatofibrosarcoma protuberans (DFSP) is a superficial fibroblastic tumor characterized by high rate of local recurrence and low metastatic potential. Fibrosarcomatous transformation can rarely arise in DFSP either de novo or as recurrent, which represents a form of tumor progression and carries an increased risk of metastasis over classic DFSP. Cytogenetically, DFSP is characterized by a recurrent unbalanced chromosome translocation t (17;22)(q22;q13), leading to the formation of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Dadone-Montaudiéet al described one pediatric pigmented DFSP, which was not found to have suspicious transcript even after using RNA sequencing, indicating that a more complicated mechanism might exist (36). There were three cases (present cases 23, 42, and 52) of genetic aberrations in the current study that could not be further identified using NGS because of the poor quality of the specimens, which could be associated with alternative rearrangement (including PDGFD rearrangement and PDGFB rearrangement with novel partner genes), cryptic COL1A1-PDGFB fusion, and even other sophisticated chromosomal aberrations (36, [49][50][51][52]. We still needed more specimens to reveal the genetic characteristics of cryptic pediatric DFSP.…”
Section: Discussionmentioning
confidence: 86%
“…Dadone-Montaudiéet al described one pediatric pigmented DFSP, which was not found to have suspicious transcript even after using RNA sequencing, indicating that a more complicated mechanism might exist (36). There were three cases (present cases 23, 42, and 52) of genetic aberrations in the current study that could not be further identified using NGS because of the poor quality of the specimens, which could be associated with alternative rearrangement (including PDGFD rearrangement and PDGFB rearrangement with novel partner genes), cryptic COL1A1-PDGFB fusion, and even other sophisticated chromosomal aberrations (36, [49][50][51][52]. We still needed more specimens to reveal the genetic characteristics of cryptic pediatric DFSP.…”
Section: Discussionmentioning
confidence: 86%
“…TNC is an extracellular matrix protein implicated in guidance of migrating neurons as well as endothelial cells, and in progression of many different types of tumors [39] . Interestingly, it also overexpressed in chondrosarcoma, Ewing sarcoma and dermatofibrosarcoma protuberans and known to promote cancer cell survival and migration as well as metastasis and malignancy therein [40][41][42][43] . Furthermore, TNC has been advocated as a potential target in STS treatment, and TNC specific ligands are available for experimental use [44] .…”
Section: Discussionmentioning
confidence: 99%
“…Leaving aside a single FS-DFSP recently reported to harbor a novel TNC-PDGFD fusion,22 we combined 22 PDGFD -rearranged DFSPs (14 published; 8 current) with known fusion partners and found that difference in 5′ partner genes might account for their clinicopathologic variations (Table 4). The major COL6A3-PDGFD fusion had a striking predominance in the trunk of females (14/16, 88%), especially the breast (7, 44%) 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…The transformation to the fibrosarcomatous (FS) variant mostly occurs de novo but varies in incidence between 5% and 20% of DFSPs with overtly increased recurrent and metastatic rates. [4][5][6] More than 90% of DFSPs harbor an unbalanced t (17;22)(q22;q13) translocation in the form of supernumerary ring chromosome or linear translocation der (22), creating the chimeric fusion of collagen type I alpha 1 chain (COL1A1) and platelet-derived growth factor subunit B (PDGFB) gene. [7][8][9] COL1A1-PDGFB fusion is formed by 5′-COL1A1 with highly variable breakpoints and 3′-PDGFB with a constant breakpoint in exon 2, resulting in a strong swapped COL1A1 promoter that upregulates expression and signaling of PDGFB in an autocrine loop.…”
mentioning
confidence: 99%